The diagnostic value of the stump impingement reflex sign for determining anterior cruciate ligament stump impingement as a cause of knee locking - Carmont Michael R; Gilbert Rob E; Marquis Christopher; Mei-Dan Omer; Rees Dai (BMC, 2012)
Abstract Background The stump impingement reflex is a subtle bounce to the knee thought to be caused by hamstring contraction when the knee is brought into extension and the torn ACL stump impinges between the distal femur and the tibial plateau. We have studied the diagnostic value of this sign. Findings From Feb 2008-Feb 2009, we audited 30 patients who underwent urgent arthroscopy for acutely locked knees. The presence of the stump impingement reflex prior to surgery was compared with the intra-operative findings. The diagnostic values of the stump impingement sign were found to be: Sensitivity 58%, Specificity 81%, Positive predictive value 70%, Negative predictive value 72% and Accuracy 71%. Conclusions We believe that the stump impingement reflex is a specific sign for ACL stump impingement as a cause of knee locking. We recommend close inspection for this sign when examining locked knees.